(3VjGA GdCfhGQ aj aVd GdYde hGdYdeGA GdCNjGQs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GaGV Ydi GdYdeGA ef ajV aVdg ehGgH GdYQaGf hHYO abO cfJ fbdJ ahGjO cKjQI hCMGOjK TgjQI JOd Ydi aVd GdYde GdebOeI GYde habfi Gddg hEjGc ddUhGH Cf GdZQV ef HYKI GdQSd GfeG gh GfJXGe CMhGd GdYHGO s
(3BNQgG (B:s
(3dGJegdhG jhe GdSQhQ Edi ZO QH ZmO jCJi HeG djS JYdehG hgPG BNQ eG JjSQ GjQGOg ai Gdbdjd ef GdGPgGf hJMUd LeYg def jfJaY Hg ef Phi GdYQaGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG Jedc dYHO GdhgGH eMahX SfI (B1143 (3hEHQGgje Mdei HGTG fLd GdNOjhi GdGcQe SfI (B1294s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs